ChemInform Abstract: Synthesis of Phenanthridin‐6(5H)‐ones via Copper‐Catalyzed Cyclization of 2‐Phenylbenzamides. Issue 36 (15th August 2013) - Gui, Qingwen; Yang, Zhiyong; Chen, Xiang; Liu, Jidan; Tan, Ze; Guo, Ruqing; Yu, Wei
Abstract The process is optimized to proceed with an inexpensive catalyst and air as the terminal oxidant.